Solid conditioner composition

By adding a specific proportion of silicate minerals, high alcohol and tetravalent ammonium amino cationic surfactants to the solid hair conditioner, the problem of melting and collapse of solid hair conditioners in high humidity environments is solved, and the effect of softening hair and maintaining performance is achieved.

JP7658723B2Active Publication Date: 2025-04-08KAWAKEN FINE CHEM CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020106153
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-06-19
Publication Date
2025-04-08
Estimated Expiration
2040-06-19

AI Technical Summary

Technical Problem

Existing solid hair conditioners are prone to melting and collapse in high humidity environments, resulting in poor performance and quality.

Method used

A solid hair conditioner combination is used that contains 1-30% by weight of silicate minerals (such as montmorillonite or chimneyite), 40-90% by weight of high alcohols (such as stearyl alcohol), and 5-20% by weight of tetravalent ammonium type cationic surfactants.

Benefits of technology

This combination allows hair conditioners to soften hair after application, rinse and dry while avoiding melting and collapse, improving product performance and quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658723000001
    Figure 0007658723000001
  • Figure 0007658723000002
    Figure 0007658723000002
Patent Text Reader

Abstract

To provide a solid conditioner composition that spreads well and can be easily applied, softens hair after application, during rinsing and after drying, is free from disintegration.SOLUTION: A solid conditioner composition containing: (A) 1 to 30 mass% of at least one kind of mineral which belongs to bentonite or smectite; (B) 40 to 90 mass% of at least one kind of higher alcohol having the fusion point of 40°C or higher; and (C) 5 to 20 mass% of at least one kind of quaternary ammonium salt type cationic surfactant, in which a moisture content is 20 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid conditioner composition which spreads well, is easy to apply, softens hair after application, rinsing and drying, and does not dissolve and crumble. [Background technology]

[0002] In recent years, from the perspective of the SDGs (Sustainable Development Goals), the reduction of packaging containers by concentrating products has been promoted. In particular, by solidifying liquid products, it is possible to eliminate plastic and simplify packaging containers, which is a very desirable form when transportation costs are taken into account. In particular, the market for conditioners and treatments is large in hair care products, and solidification is a great advantage. However, solidification can cause problems with performance and quality deterioration. In terms of performance, silicone oils and ester oils that make hair smooth are mainly liquid, so they cannot be blended in large quantities and their performance is currently poor. In addition, in terms of quality, there is also a problem of disintegration due to contact with moisture during use. Patent Document 1 proposes a solid hair conditioner composition that contains (i) at least 5% by weight of a cationic surfactant and (ii) at least 5% by weight of a fatty alcohol material, and contains less than 80% by weight of water. This solid hair conditioner composition has performance similar to that of a liquid conditioner, but it may disintegrate when stored in a bathroom with high humidity, and there have been cases where satisfactory performance was not obtained in terms of quality. That is, in the case of solid conditioner compositions, there have been cases where the performance and quality of the compositions, which are easy to spread and apply, soften the hair after application, rinsing, and drying, and do not dissolve and crumble, have been unsatisfactory. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2004-534807 Summary of the Invention [Problem to be solved by the invention]

[0004] In order to solve such problems, the main object of the present invention is to provide a solid conditioner composition that spreads well, is easy to apply, softens hair after application, rinsing, and drying, and does not dissolve and crumble. [Means for solving the problem]

[0005] The present inventors conducted extensive research to solve the above problems and discovered that a solid conditioner composition containing a specific powder spreads well and is easy to apply, and softens hair after application, rinsing, and drying, preventing it from dissolving and crumbling, which led to the completion of the present invention.

[0006] That is, the present invention is as follows. (1) (A) 1 to 30% by weight of at least one mineral belonging to bentonite or smectite; (B) 40 to 90% by weight of at least one higher alcohol having a melting point of 40° C. or higher; (C) 5 to 20% by weight of at least one quaternary ammonium salt type cationic surfactant and a water content of 20% by weight or less. (2) The solid conditioner composition of (1), wherein component (A) is montmorillonite. (3) Furthermore, the present invention is directed to a solid conditioner composition according to (1) or (2), in which component (C) is a quaternary ammonium methosulfate salt. Effect of the Invention

[0007] According to the present invention, by blending a specific powder, it is possible to provide a solid conditioner composition which spreads well and is easy to apply, softens hair after application, rinsing, and drying, and does not dissolve or crumble. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, an embodiment of the present invention will be described. The bentonite or smectite minerals, which are component (A), are blended in the form of powder into the solid conditioner composition. Bentonite is the name of a clay rock that contains montmorillonite as the main component, quartz, α-cristobalite, opal and other silicate minerals as secondary components, and is accompanied by feldspar, mica, zeolite and other silicate minerals, calcite, dolomite, gypsum and other carbonate minerals and sulfate minerals, as well as pyrite and other sulfide minerals. Smectite is the name of a group of clay minerals, including montmorillonite, beidellite, nontronite, saponite, and hectorite. Bentonite, or minerals belonging to smectite, has water-blocking and thickening effects for industrial purposes, and is widely used in soil and water pollution countermeasures, environmental restoration, disaster prevention, etc. It is also known for its softening effect on clothes, and there are also products that claim to have a softening effect when added to powder laundry detergent. However, hair conditioners that are intended to have a softening effect are generally liquid, and when these ingredients are mixed in large quantities, they thicken and can cause quality problems. On the other hand, in the case of solid conditioners, higher alcohols, quaternary ammonium salt-type cationic surfactants, oils and fats, etc. are melted at high temperatures and solidified while emulsifying, but the humidity and temperature can cause the conditioner to disintegrate. Therefore, adding bentonite or a mineral belonging to smectite, which is component (A), can significantly improve the disintegration. Furthermore, the softening effect on hair from application to rinsing is also improved. In the case of bentonite, it is desirable to remove as many of the minor components as possible, since the main component, montmorillonite, exerts the above effects. In addition, in the case of smectite, montmorillonite and hectorite are desirable.

[0009] Bentonite or smectite minerals may be used alone or in combination of two or more. Bentonite or smectite minerals may disintegrate when added in an amount of less than 1% by weight. Bentonite or smectite minerals suppress disintegration and exhibit a hair softening effect when added in an amount of 1% by weight or more. Furthermore, disintegration can be suppressed without the influence of other ingredients when added in an amount of 5% by weight or more. On the other hand, when added in an amount of more than 30% by weight, disintegration may not occur even with the water at the time of use, and the performance as a conditioner may decrease, so 25% by weight or less is preferable. That is, 5 to 25% by weight is preferable to suppress disintegration and maximize the hair softening effect.

[0010] Examples of the higher alcohol having a melting point of 40°C or higher, which is the component (B), include cetanol, stearyl alcohol, arachyl alcohol, and behenyl alcohol. One or more types of higher alcohol may be used in combination. Myristyl alcohol, which has a melting point of 38°C, may also be added as long as the melting point of all the higher alcohols mixed together is 40°C or higher. The solid conditioner composition of the present invention can improve the softness of hair after application, rinsing, and drying, and can provide the effect of preventing disintegration during storage. However, disintegration may not be prevented if the composition is in contact with moisture for a long time. Furthermore, if the melting point of the higher alcohol is less than 40°C, disintegration may occur in a short time in a hot and humid bathroom. In order to further prevent disintegration, a higher alcohol with a melting point of 45°C or more is preferable. If the higher alcohol is not blended at 40% by weight or more, disintegration due to the influence of other components with low melting points may not be suppressed, and more preferably, 50% by weight or more is preferable. Moreover, if the higher alcohol is blended at more than 90% by weight, it may not dissolve during use and may not provide the desired performance. More preferably, the content is 80% by weight or less. That is, 50 to 80% by weight is more preferable because it provides a good balance between prevention of disintegration and performance as a conditioner.

[0011] Examples of the quaternary ammonium salt type cationic surfactant which is the component (C) include behentrimonium methosulfate, steartrimonium methosulfate, cetrimonium methosulfate, behenamidopropyltrimonium methosulfate, ricinoleamidopropyltrimonium methosulfate, babassuamidopropyltrimonium methosulfate, palmamidopropyltrimonium methosulfate, stearyl ethylhexyldimonium methosulfate, dioleoylethylhydroxyethylmonium methosulfate, distearate, Aroyl ethyl hydroxyethylmonium methosulfate, di-soybean oil fatty acid ethyl hydroxyethylmonium methosulfate, di-rapeseed oil fatty acid ethyl hydroxyethylmonium methosulfate, dipermoyl ethyl hydroxyethylmonium methosulfate, dihydrogenated permoyl ethyl hydroxyethylmonium methosulfate, dipalmitoyl ethyl hydroxyethylmonium methosulfate, bis((isostearoyl / oleoyl)isopropyl)dimonium methosulfate, bis(soybean oil fatty acid / rapeseed oil fatty acid)ethyl hyaluronate Quaternary ammonium methosulfate salts such as hydroxyethylmonium methosulfate, bis(ethyl behenate PPG-3)dimonium methosulfate, PEG-2 dimeadowfoam amidoethylmonium methosulfate, PEG-3 dioleoyl amidoethylmonium methosulfate, PEG-3 distearoyl amidoethylmonium methosulfate, behenyl trimethyl ammonium chloride (behentrimonium chloride), myristyl trimethyl ammonium chloride, myristyl trimethyl ammonium bromide, cetyl trimethyl ammonium chloride Examples of quaternary ammonium halide salts include quaternary ammonium halide salts such as ammonium bromide, cetyltrimethylammonium bromide, stearyltrimethylammonium chloride, stearyltrimethylammonium bromide, behenyltrimethylammonium bromide, myristyldimethylbenzylammonium chloride, cetyldimethylbenzylammonium chloride, stearyldimethylbenzylammonium chloride, 2-decyltetradecyltrimethylammonium chloride, 2-dodecylhexadecyltrimethylammonium chloride, distearyldimethylammonium chloride, and dicetyldimethylammonium chloride.

[0012] These quaternary ammonium salt type cationic surfactants improve the feel of application to hair, spreadability on hair, and softness during rinsing. In addition, by remaining on hair after drying, hair flexibility and antistatic effects can be obtained. One or more types of (C) component may be used in combination. If the (C) component is not blended at 5% by weight or more, these effects may not be observed. Preferably, it is 8% by weight or more. Quaternary ammonium salt type cationic surfactants may be highly water-soluble, and if it exceeds 20% by weight, it may dissolve and collapse. In addition, quaternary ammonium salt type cationic surfactants may be highly irritating. The quaternary ammonium salt type cationic surfactant is preferably 20% by weight or less, more preferably 15% by weight or less. In addition, generally, quaternary ammonium salt cationic surfactants are solid at room temperature and are often provided in a mixture with water or ethanol, and when a large amount of quaternary ammonium salt cationic surfactant is added, the liquid content increases accordingly. In order to maintain a solid state that does not dissolve and crumble, the amount added may naturally be limited. Among quaternary ammonium salt cationic surfactants, quaternary ammonium methosulfate salts are more preferred because they are provided in pellet form as a mixture with component (B).

[0013] Water is an optional component, and may be added by adding a water-soluble component. The water content in the solid conditioner composition is preferably 20% by weight or less, more preferably 15% by weight or less, and may not be added. If the water content exceeds 20% by weight, the solid may soften, making molding difficult and causing disintegration.

[0014] The solid conditioner composition of the present invention can contain ingredients that are typically used in liquid conditioners. For example, silicones such as highly polymerized dimethylpolysiloxane, dimethylpolysiloxane oil, cyclic silicone, amino-modified silicone, polyether-modified silicone, methylphenylpolysiloxane, fatty acid-modified silicone, alcohol-modified silicone, alkoxy-modified silicone, epoxy-modified silicone, fluorine-modified silicone, and alkyl-modified silicone; nonionic surfactants such as fatty acid alkanolamide, polyoxyalkylene fatty acid alkanolamide, polyoxyethylene hydrogenated castor oil, polyoxyethylene alkyl ether, polyoxyethylene sorbitan fatty acid ester, glycerin fatty acid ester, polyglycerin fatty acid ester, sucrose fatty acid ester, polyglycerin alkyl ether, and alkyl glycoside; moisturizers such as trehalose, hyaluronic acid, collagen, and carboxymethyl chitosan succinamide; aloe vera extract, Scutellaria root extract, Panax ginseng extract, persimmon tannin extract, canina rose extract, chamomile flower extract, white lady's foot extract, pear branch extract, centifolia Extracts such as ribeye extract, tea leaf extract, heartflower extract, witch hazel extract, tilia cordata extract, mulberry extract, cornflower extract, yuzu extract, Roman chamomile extract, royal jelly extract, turmeric extract, ginseng extract, hibamata extract, beech bud extract, rice bran extract, camellia extract, peach kernel extract, sophora flavescens extract, chlorella extract, marjoram extract, yarrow extract, shell ginger leaf extract, Phellodendron bark extract, Coptis japonica extract, Pueraria lobata extract, Lithospermum ulmoides extract, peony extract extracts from natural products such as swertia japonica extract, birch extract, sage extract, loquat extract, carrot extract, aloe extract, mallow extract, iris extract, grape extract, coix seed extract, loofah extract, lily extract, saffron extract, cnidium rhizome extract, ginger extract, hypericum extract, rosemary extract, garlic extract, chili pepper extract, and sanguisorba extract; natural product extracts; proteins or hydrolysates thereof obtained from shells or pearls having nacre;Examples of the agent include proteins obtained from silk or hydrolysates thereof, protein-containing extracts obtained from the seeds of legumes, polymer compounds such as cationic cellulose and hydroxylated cellulose, antidandruff agents such as zinc pyrithione, trichlorocarbanilide, sulfur, isopropylmethylphenol, and benzalkonium chloride, emulsifiers, opacifiers, sequestering agents, UV absorbers, antioxidants, preservatives, powdered components, blood circulation promoters, local stimulants, hair follicle activators, hair nutrients, antiandrogenic agents, antiseborrheic agents, antiaging agents, emollients, keratolytic agents, bactericides, preservatives such as phenoxyethanol and parabens, anti-inflammatory agents, anti-inflammatory agents, cooling agents, amino acids, vitamins, and herbal extracts, as well as hair growth agents, pH adjusters, pigments, dyes, coloring materials, and fragrances. However, highly hydrophilic ingredients and ingredients that are liquid at room temperature can cause the composition to melt and crumble, so they are mixed in an amount that does not affect the composition's performance. In addition, the water content in the solid conditioner composition must not exceed 20% by weight.In addition, isopropyl palmitate, octyl palmitate, isopropyl myristate, myristyl myristate, stearyl stearate, isocetyl stearate, isononyl isononanoate, isotridecyl isononanoate, hydrogenated castor oil stearate, hydrogenated castor oil hydroxystearate, glyceryl tri-2-ethylhexanoate, pentaerythritol tetra-2-ethylhexanoate, neopentyl glycol dicaprate, diglyceryl diisostearate, dipentaerythritol and hydroxystearate / stearate. Ester oils such as esters with mixed fatty acids such as stearic acid / rosin acid, isopropyl lauroyl sarcosine, phytosteryl / behenyl / octyldodecyl / isostearyl lauroyl glutamate, di(cholesteryl / behenyl / octyldodecyl) lauroyl glutamate, diisostearyl lauroyl glutamate, dioctyldodeceth-2 lauroyl glutamate, disteareth-2 lauroyl glutamate, dihexyldecyl lauroyl glutamate, 18-methyleicosanoic acid, 1 Branched fatty acids such as 4-methylpentadecanoic acid, 14-methylhexadecanoic acid, 15-methylhexadecanoic acid, 15-methylheptadecanoic acid, 16-methylheptadecanoic acid, 16-methyloctadecanoic acid, 17-methyloctadecanoic acid, and 17-methylnonadecanoic acid, as well as their ester oils, lanolin fatty acids and their salts and other lanolin extracts, natural ceramides or natural ceramides and their derivatives, olive oil, camellia oil, macadamia nut oil, corn oil, avocado oil, castor oil, safflower oil, jojoba oil, sunflower oil, Natural oils such as rapeseed oil, sesame oil, soybean oil, and meadowfoam oil; various oils and fats such as hydrocarbon oils such as liquid paraffin, liquid isoparaffin, petrolatum, squalene, and squalane; lower alcohols such as ethanol and isopropanol; and polyols such as glycerin, diglycerin, diethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, 1,3-butylene glycol, pentylene glycol, pentaerythritol, and sorbitol can also be blended to the extent that they do not promote disintegration.

[0015] The solid conditioner composition of the present invention does not exhibit fluidity at room temperature (25°C) and normal pressure (1 atm), and its shape is not particularly limited. Specific examples of the shape include stick-shaped, rod-shaped, plate-shaped, and poured into a container. These various solid conditioner compositions can be prepared according to a conventional method. For example, all raw materials are heated to above the melting point, mixed uniformly, and then water-soluble components are added while cooling, and the molten state is poured into a specified container such as a jar container, a metal dish, or a resin dish, and cooled or allowed to cool to form a solid conditioner composition. It can also be filled into a stick container to form a stick shape. EXAMPLES

[0016] The effects of the present invention will be described in more detail with reference to the following examples, but the present invention is not limited to these examples. In the following description, the blending amount in the formulation is expressed as % by weight based on the total amount unless otherwise specified. In the following examples and comparative examples, the solid conditioner composition of the present invention was evaluated as follows.

[0017] The solid conditioner compositions shown in Tables 1 and 2 were prepared according to the following manufacturing procedures. (Manufacturing Procedure) (1) Heat all the ingredients shown in Tables 1 and 2 to approximately 90°C and mix uniformly. (2) Pour the mixture into a cylindrical tube 5 cm in diameter and 50 cm in height, with a lid on the bottom, and allow to cool. (3) After the mixture had cooled to room temperature and solidified, it was extruded from the tube and cut into pieces 3 cm wide. The following evaluations were carried out. All of the solid conditioner compositions shown in Tables 1 and 2 were in a solid state at room temperature.

[0018] (Performance evaluation) The performance evaluation was carried out by eight female expert panelists who used the solid conditioner compositions of the Examples and Comparative Examples five times and judged them on a five-point scale. The average was shown as the result. (Ease of application) Poor spreadability makes it difficult to apply: 1 point; Poor spreadability makes it difficult to apply: 2 points; Normal spreadability: 3 points; Good spreadability and easy application: 4 points; Very good spreadability and very easy application: 5 points For examples where coating was not possible, the following performance evaluation was discontinued. (Hair softness after application) Worse than before application: 1 point, slightly worse than before application: 2 points, unchanged from before application: 3 points, slightly softer than before application: 4 points, softer than before application: 5 points (Hair softness when rinsing) Worse than before application: 1 point, slightly worse than before application: 2 points, unchanged from before application: 3 points, slightly softer than before application: 4 points, softer than before application: 5 points (Hair softness after drying) Worse than before use: 1 point, slightly worse than before use: 2 points, unchanged from before use: 3 points, slightly softer than before use: 4 points, softer than before use: 5 points

[0019] (Quality Evaluation) Assuming storage conditions in a bathroom, we checked whether the product would dissolve and crumble under high humidity conditions. Storage conditions: 25°C, 80% humidity. Leave for 24 hours to check for surface melting and crumbling. ×: More than half of the product has melted and crumbled; △: The surface has melted and crumbled; ◯: The surface has softened but there is no melting or crumbling We verified whether the material would disintegrate under high temperature and humidity conditions, assuming conditions of actual use. In addition, since the composition cannot be applied if it does not dissolve at all during use, those that do not dissolve at all were also marked as x. Storage conditions: 40℃, 80% humidity, left for 1 hour, surface melting and crumbling confirmed ×: Disintegrated into a paste or not at all, △: More than half of the mixture was dissolved and disintegrated, ◯: Disintegration occurred on the surface (Dissolves and recovers) We checked whether it could withstand repeated use. Storage conditions: 40°C, 80% humidity, left for 1 hour, then 25°C, 80% humidity, left for 24 hours, repeated three times, and the product was checked for disintegration. ×: Melted and crumbled into a paste, △: More than half of it melted and crumbled, ◯: The surface became soft but it did not melt and crumble.

[0020] Working Example [Table 1]

[0021] Bentonite: Kunimine Kogyo Co., Ltd. MoistNite (registered trademark) S Hectorite Kunimine Kogyo Co., Ltd. Sumecton (registered trademark) SWN Behentrimonium methosulfate Croda Japan Co., Ltd. Incroquat (registered trademark) Behenyl TMS (Composition: Behentrimonium methosulfate 30% by weight, stearyl alcohol 35% by weight, cetanol 35% by weight) Stearyl alcohol Kao Corporation Kalcol (registered trademark) 8098 Cetanol Kao Corporation Kalcol 6098 Behentrimonium chloride Nikko Chemicals Co., Ltd. NIKKOL (registered trademark) CA-2580 (Composition: behentrimonium chloride 80% by weight, ethanol 20% by weight) Olive oil NIKKOL Olive Oil by Nikko Chemicals

[0022] Comparative Example [Table 2]

[0023] Evaluation Results Examples 1 to 8 prepared within the range of the solid conditioner composition of the present invention were excellent in performance and quality evaluation, with good spreadability, easy application, softening hair after application, rinsing, and drying, and no disintegration. On the other hand, in Comparative Example 1, in which the (A) component was not blended, the softness of the hair after application and rinsing was poor, and the evaluations of disintegration and disintegration recovery assuming storage conditions in a bathroom were poor. In Comparative Example 2, in which the melting point of the higher alcohol was less than 40°C, the evaluations of disintegration and disintegration recovery were poor. In Comparative Example 3, in which the (C) component was below the range, the hair softness was poor. In Comparative Example 4, in which the (A) component was beyond the range, the composition did not disintegrate at all during use and could not be applied. In Comparative Example 5, in which the (C) component was beyond the range, the evaluations of disintegration and disintegration recovery were poor. In Comparative Example 6, in which the water content was beyond the range, the evaluations of disintegration and disintegration recovery were poor. [Industrial Applicability]

[0024] The solid conditioner composition of the present invention spreads well and is easy to apply, softens hair after application, rinsing, and drying, does not dissolve, and has excellent performance and quality, thereby increasing the commercial value of solid conditioners, solid rinses, solid treatments, etc.

Claims

1. (A) 10 to 30% by weight of at least one mineral selected from the group consisting of bentonite and smectite; (B) 40 to 80% by weight of at least one higher alcohol having a melting point of 40° C. or higher; (C) at least one quaternary ammonium salt type cationic surfactant in an amount of 5 to 20% by weight; A solid conditioner composition having a water content of 20% by weight or less.

2. 2. The solid conditioner composition according to claim 1, wherein component (A) is montmorillonite.

3. 3. The solid conditioner composition according to claim 1, further comprising component (C) being a quaternary ammonium methosulfate salt.

Citation Information

Patent Citations

  • Fatty acid soap containing clay minerals

    JP1997087687A

  • Solid soap comprising bentonite

    JP2003138295A

  • Hair conditioning composition

    JP2004534807A

  • Solid soap

    JP2005082685A

  • Soap

    JP2019104784A